2008
DOI: 10.1371/journal.pbio.0060309
|View full text |Cite
|
Sign up to set email alerts
|

Microsporidia Are Natural Intracellular Parasites of the Nematode Caenorhabditis elegans

Abstract: For decades the soil nematode Caenorhabditis elegans has been an important model system for biology, but little is known about its natural ecology. Recently, C. elegans has become the focus of studies of innate immunity and several pathogens have been shown to cause lethal intestinal infections in C. elegans. However none of these pathogens has been shown to invade nematode intestinal cells, and no pathogen has been isolated from wild-caught C. elegans. Here we describe an intracellular pathogen isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
403
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(420 citation statements)
references
References 59 publications
(95 reference statements)
15
403
2
Order By: Relevance
“…IFs may also provide a protective barrier against various pathogens. Thus, a discontinuous endotube with large intermittent gaps was found in worms whose intestinal cells were infected with microsporidia [Troemel et al, 2008].…”
Section: Intermediate Filaments In the C Elegans Intestinementioning
confidence: 98%
“…IFs may also provide a protective barrier against various pathogens. Thus, a discontinuous endotube with large intermittent gaps was found in worms whose intestinal cells were infected with microsporidia [Troemel et al, 2008].…”
Section: Intermediate Filaments In the C Elegans Intestinementioning
confidence: 98%
“…Drechmeria coniospora, Nematocida parisii, Candida albicans) and also a nodavirus (Orsay virus) [6]. Some of the used pathogens interact with C. elegans in nature, especially the microsporidian N. parisii [7], Orsay virus [8], P. aeruginosa [9], Leucobacter sp. [10], and possibly also M. nematophilum and B. thuringiensis.…”
Section: Brief Overview Of the Caenorhabditis Elegans Immune Systemmentioning
confidence: 99%
“…Nevertheless, a few pathogens show different infection characteristics. The microsporidian N. parisii and Orsay virus are intracellular pathogens [7,8] cuticle; the latter two via the anal region and tail, and the former mainly via the mouth, the vulva and the anus [10][11][12]. These pathogens therefore target distinct tissues to those infecting the gut.…”
Section: Brief Overview Of the Caenorhabditis Elegans Immune Systemmentioning
confidence: 99%
“…C. elegans is transparent, which facilitates analysis of infection in these cells within intact animals. We recently described a natural intracellular pathogen that infects the C. elegans intestine and showed that this pathogen defines a new genus and species of microsporidia, which are obligate, fungal-related intracellular pathogens (9,10). The microsporidia phylum comprises more than 1,400 species of pathogens that can infect a wide variety of animals including humans, where they commonly infect the intestine and can cause lethal diarrhea in immunocompromised hosts (11,12).…”
mentioning
confidence: 99%
“…We named the C. elegans-infecting species of microsporidia Nematocida parisii, or nematode killer from Paris, because it was isolated from wild-caught C. elegans in a compost pit near Paris and it eventually kills its host. Wild-caught Caenorhabditis nematodes infected with microsporidia have been isolated from environmental regions around the globe, indicating that microsporidia are a common cause of infection for C. elegans in the wild (9,13).…”
mentioning
confidence: 99%